A systematic review of long-distance triathlon musculoskeletal injuries - Rhind, J.-H.; Dass, D.; Barnett, A.; Carmont, M. (Journal of Human Kinetics, 2022)
The distribution of injuries affecting long-distance triathletes is yet to be fully understood. A systematic review was performed of the clinical literature to determine the epidemiology of musculoskeletal injuries affecting long-distance triathletes. Searched databases in Feb 2020 were PubMed, Medline, EMBASE, EMCARE, and CINHAL databases. Published observational research articles related to the incidence or prevalence of musculoskeletal injuries in long-distance triathletes (competing at "Ironman" full distance or greater), written in the English language and not restricted by age or gender or date were eligible. Of the 975 studies identified on the initial search, six studies met the inclusion criteria for analysis. The mean age (SD) of the long-distance triathletes in these studies was 35.1 (2.7) and the range was 21-68 years. Overuse injuries were most frequent with the incidence range of 37-91%, and acute injury incidence range was 24-27%. The knee and spine were the most frequent location of injury. Running and cycling were the most frequently affected disciplines. Elite athletes had a lower incidence of overuse injury (37%). The highest acute injury incidence (27%) was recorded in non-elite athletes. The quality of the studies was relatively poor with only one study satisfying >50% of the quality assessment tool questions and only two studies were prospective, the rest were retrospective cross-sectional studies. Overall, there is a lack of literature reporting on musculoskeletal injuries in long-distance triathletes. Overuse injuries, particularly in the knee, are the most frequently reported, running and cycling are the most frequent disciplines associated. Long-distance triathletes may have a lower incidence of both overuse and acute injuries.